Penguatan Keterampilan Melalui Pelatihan Pengembangan Ide Bisnis di SMK Tri Sukses, Kota Depok - Rusiyati, Sri; Elyana, Instianti; Zuniarti, Ida; Candrasari, Ati (Indonesian Journal of Society Engagement, 2024)
Vocational high school institution, SMK Tri Sukses Depok has an important role in preparing its students to face the world of work or become independent entrepreneurs by providing students with entrepreneurial skills, ranging from identifying business opportunities to preparing sustainable business plans. The purpose of this activity is to develop creative and innovative ideas in creating independent business opportunities, which are expected to improve students' abilities in facing future competition and fostering an entrepreneurial spirit. The method used is to conduct training accompanied by simulations and case studies to develop creative and innovative ideas so that they are ready to face the challenges of the world of work or create independent business opportunities. The training uses learning modules, internet access, projectors, and laptops for presentations. The results of the training showed that there was an increase in participants' knowledge, creativity and innovation in entrepreneurial skills, ranging from identifying business opportunities to preparing business plans and students were motivated to start entrepreneurship. The responses of the training participants were very satisfied and very interested in participating again in the next activity.